A density functional theory study of the role of functionalized graphene particles as effective additives in power cable insulation. Issue 2 (7th February 2018) - Song, Shuwei; Zhao, Hong; Zheng, Xiaonan; Zhang, Hui; Liu, Yang; Wang, Ying; Han, Baozhong
Abstract : The role of a series of functionalized graphene additives in power cable insulation in suppressing the growth of electrical treeing and preventing the degradation of the polymer matrix has been investigated by density functional theory calculations. Bader charge analysis indicates that pristine, doped or defect graphene could effectively capture hot electrons to block their attack on cross-linked polyethylene (XLPE) because of the π–π conjugated unsaturated structures. Further exploration of the electronic properties in the interfacial region between the additives and XLPE shows that N-doped single-vacancy graphene, graphene oxide and B-, N-, Si- or P-doped graphene oxide have relatively strong physical interaction with XLPE to restrict its mobility and rather weak chemical activity to prevent the cleavage of the C–H or C–C bond, suggesting that they are all potential candidates as effective additives. The understanding of the features of functionalized graphene additives in trapping electrons and interfacial interaction will assist in the screening of promising additives as voltage stabilizers in power cables.